112 Blood spot testing for late onset pompe disease. Issue 6 (24th May 2018) - Dobbins, Julia; Pyragius, Tim; Brion, Kristian; Chin, Sharon; Gurner, Melissa; Pacyna, Janina; Stark, Samantha; Fletcher, Janice M
Abstract : Introduction: Pompe disease is classified by age of onset and presentation. Late-onset Pompe disease (LOPD) generally presents with progressive limb-girdle and respiratory muscle weakness. Diagnosis is confirmed following dried blood spot (DBS) enzyme assay by a second method, either mutation or glucose tetra-saccharide analysis. Methods: From 2000 to 2016, acid α –glucosidase ( GAA ) activity in DBS was measured using the immuno-capture assay of . Umapathysivam et al. (2001) From 2016 testing used the multiplex tandem mass spectrometry method (6-PLEX LC-MSMS, Perkin Elmer), measuring six lysosomal storage disease enzymes from one DBS. Glucose tetra-saccharides were measured by mass spectrometry and mutation analysis of the GAA gene was performed using either Sanger or Next Generation Sequencing, the latter confirmed by sequencing. Results: Between 2000 and 2016, approximately 1500 samples were screened for Pompe disease with 77 positives, a diagnosis rate of 5.1%. Of these, 33 were infantile Pompe disease, with 44 LOPD. Since May 2016, a further 850 patients have been screened for Pompe disease using the MSMS method and of these, 28 patients have screened as positive, with 19 confirmed as having Pompe disease, either by molecular testing or urine tetra-saccharide measurement, a diagnosis rate of 2.2%. Of these 19 patients, 17 are LOPD, with only two infants being diagnosed in this time. Seven adults are still to be confirmed by a second test. Conclusion: The number of patients presenting for testing follows the recent Australian government funding for enzyme replacement therapy for adults with LOPD. The ease of submitting a dried blood spot sample for testing has contributed to an increase in test requests, although this may also reflect an increased recognition of this condition. These patients may have already been diagnosed clinically, but in the absence of a treatment, there was little benefit in a formal diagnosis.